Environmental conditions for alternative tree-cover states in high latitudes - Abis, Beniamino; Brovkin, Victor (Biogeosciences, 2017)
Previous analysis of the vegetation cover from remote sensing revealed the existence of three alternative modes in the frequency distribution of boreal tree cover: a sparsely vegetated treeless state, an open woodland state, and a forest state. Identifying which are the regions subject to multimodality, and assessing which are the main factors underlying their existence, is important to project future change of natural vegetation cover and its effect on climate.We study the link between the tree-cover fraction distribution and eight globally observed environmental factors: mean annual rainfall, mean minimum temperature, growing degree days above 0 °C, permafrost distribution, mean spring soil moisture, wildfire occurrence frequency, soil texture, and mean thawing depth. Through the use of generalised additive models, conditional histograms, and phase-space analysis, we find that environmental conditions exert a strong control over the tree-cover distribution, uniquely determining its state among the three dominant modes in  ∼  95 % of the cases. Additionally, we find that the link between individual environmental variables and tree cover is different within the four boreal regions considered here, namely eastern North Eurasia, western North Eurasia, eastern North America, and western North America. Furthermore, using a classification based on rainfall, minimum temperatures, permafrost distribution, soil moisture, wildfire frequency, and soil texture, we show the location of areas with potentially alternative tree-cover states under the same environmental conditions in the boreal region. These areas, although encompassing a minor fraction of the boreal area ( ∼  5 %), correspond to possible transition zones with a reduced resilience to disturbances. Hence, they are of interest for a more detailed analysis of land–atmosphere interactions.